Identification of Lake Perintis Tourism Development Opportunities in Huluduotamo Village, Suwawa Sub District, Bone Bolango Regency - Yusuf, Nilawaty; Wunarlan, Irwan (AIBPM Publisher, 2019)
The Suwawa City is a city of services, commerce and customs. The city of services embedded in the Suwawa City gave him opportunity to develop tourism services. Local governments and stakeholders in the tourism sector have not been optimal and comprehensive in managing tourism objects in Bone Bolango Regency so that tourism sector's contribution to formation of the GRDP structure is low. Pirintis Lake has opportunity to be developed into one of natural attractions destinations. Development of Perintis Lake is expected to be able to increase domestic and foreign tourist visits so as to provide an multiplier effect for tourism and regional economic entrepreneurs. This study aims to examine the development strategy, potential and supporting facilities of Perintis Lake natural tourism objects. This study uses a quantitative descriptive model, focusing on Perintis Lake. Primary data were collected using a questionnaire while accidental sampling was used to determine the number of samples. The number of samples was 62 respondents. Alternative answers in the questionnaire are set using the Likert scale. The data analysis techniques use score and SWOT intervals. SO strategy (Strenght-Opportunity) or aggressive strategy is the right strategy to be used to develop Perintis Lake natural attractions because Perintis Lake natural tourism objects are potential enough to be developed into tourist destinations so that tourism services and foreign exchange outcomes are optimal also. Keywords: Suwawa city, Perintis lake, natural tourism, tourist visits